THE FIRE NEXT TIME: LAND USE PLANNING IN THE WILDLAND/URBAN INTERFACE (Utah Environmental Law Review; Vol 28 No 2 (2008))
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Wildfire is a growing threat to suburban and exurban communities, in part because fires have grown more severe and frequent as a result of land use and climatic influences and in part because more people are living in fire prone areas.   Unfortunately, the so-called Healthy Forest Restoration Act (HFRA), the federal government’s response to this crisis, is a deeply flawed statute that will likely exacerbate wildfire risks at the same time it makes real ecological restoration even harder.   While HFRA took halting, partial steps toward the integration of broad and small scale land use planning, it was clearly still the outgrowth of the dysfunctional legislative process in Washington.   Before the governance of public lands adapts too completely to HFRA, this law should be overhauled or repealed.